Quality of life and physical activity in elderly people: Autonomy, social participation and well-being - Claudia Maulini; Emanuele Federici; Mascia Migliorati; Enrico Miatto (Pensa MultiMedia, 2022)
The article presents the results of the qualitative survey "Quality of life and physical activity in Elderly People" which aimed to investigate the influence of physical activity on the quality of life of the elderly people. Five focus groups were carried out to find out the opinion of 35 participants of an exercise programme in an Italian center for training and introduction to sport. The content analysis was carried out through the application of the Schalock and Verdugo's Quality of Life Scale. The survey showed that participation in this physical activity programme enabled participants to counteract the onset of physical and physiological age-related limitations; it favoured processes of personal and community empowerment, positively affecting aspects relating to the emotional and psychological dimension, the development of self-esteem and self-efficacy, the management of relational dynamics and promoting participation, social inclusion and the establishment of meaningful relationships.